Pengaruh Ukuran Perusahaan, Kompleksitas Audit, Risiko Perusahaan, Dan Ukuran Kap Terhadap Fee Audit: - Nova Yulianti; Henri Agustin; Salma Taqwa (Jurnal Eksplorasi Akuntansi, 2019)
This study aims to determine: (1) The effect of company size on audit fee, (2) The effect of audit complexity on audit fee, (3) The effect of company risk on audit fee, (4) The effect of KAP size on audit fee. Population in this research are non financial companies listed in Indonesia Stock Exchange (IDX) in 2014 – 2017. The sample is determined based on purposive sampling method with a total sample of 68 companiees. The data used in this research is secondary data. The technique of collecting data by the method of documentation at www.idx.com and the official website of each company. The analytical method used is multiple regression analysis. The result showed that: (1) Company size influence a significant positive on audit fee, (2) Audit complexity influence a significant positive on audit fee, (3) Company risk no significant effect on audit fee, and (4) KAP size influence a significant positive on audit fee.